Advances in Citrus Nutrition 2012
DOI: 10.1007/978-94-007-4171-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant and Nutrient Uptake in Citrus

Abstract: Generally roots not only provide anchorage and support to plants but also help to absorb water and nutrients from the soil. The roots and shoots of plants including citrus are functionally separate but mutually dependent. The roots absorb water and mineral nutrients from the soil and transport to the areal parts including shoots and leaves. In return the shoots supply photosynthates to the roots. Presently the need of absorption of inorganic nutrients through plant leaves has AbstractThe availability of essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(72 reference statements)
3
8
0
Order By: Relevance
“…fivefold higher than that in the external solution (estimation based on the tissue water content; details not shown). This cellular 134 Cs concentration suggests active uptake mechanisms involved in 134 Cs foliar uptake from the leaf apoplastic space to the cytosol, as has been indicated for other cations (Wójcik, ; Singh & Khan, ). The K transporter OsHAK5, whose expression in the leaf plasma membrane of rice has been revealed (Yang et al ., ), might contribute to the active foliar uptake of 134 Cs we observed, because the HAK transporters generally discriminate weakly for Cs over K (Véry et al ., ).…”
Section: Discussionsupporting
confidence: 64%
“…fivefold higher than that in the external solution (estimation based on the tissue water content; details not shown). This cellular 134 Cs concentration suggests active uptake mechanisms involved in 134 Cs foliar uptake from the leaf apoplastic space to the cytosol, as has been indicated for other cations (Wójcik, ; Singh & Khan, ). The K transporter OsHAK5, whose expression in the leaf plasma membrane of rice has been revealed (Yang et al ., ), might contribute to the active foliar uptake of 134 Cs we observed, because the HAK transporters generally discriminate weakly for Cs over K (Véry et al ., ).…”
Section: Discussionsupporting
confidence: 64%
“…Skin damages observed on citrus fruits during storage are mainly caused by potassium deficiency. It is confirmed that foliar application of Ca reduces skin discoloration in citrus fruits (Smoleń 2012;Singh and Khan 2012;Gimeno et al 2014). …”
Section: Foliar Nutrition and Postharvest Quality Of Cropsupporting
confidence: 58%
“…Cañamás, et al (2008) obtained a similar result by using of Fungicover as adjuvant, which seems to bring a protective effect to the biocontrol agent against adverse environmental conditions. Surfactants as Tween 80 are generally used into the solution to improve its performance and effectiveness, those compounds cause reduction in surface tension and alter the energy relationships at interfaces, due to presence of both hydrophobic and hydrophilic group within the same molecule, these compounds adjust themselves as interfaces (Singh and Khan, 2012). On the other hand, a simple and efficient method to improve antagonistic activity is the use of additives like sucrose and yeast extract to increase the population and enhance the survival rate of the microbial antagonist (Ippolito and Nigro, 2000).…”
Section: Population Dynamics Of Biological Control Agentmentioning
confidence: 99%